Coping with perceived ethnic prejudice on the gay scene. Issue 2 (3rd April 2017) - Jaspal, Rusi
ABSTRACT: There has been only cursory research into the sociological and psychological aspects of ethnic/racial discrimination among ethnic minority gay and bisexual men, and none that focuses specifically upon British ethnic minority gay men. This article focuses on perceptions of intergroup relations on the gay scene among young British South Asian gay men and the effects of perceived prejudice for their identities. Twelve young British South Asian gay men were interviewed about their experiences. The qualitative data were analyzed using thematic analysis, which yielded the following themes: (a) ethnic otherization on the gay scene, (b) mechanisms of rejection on the gay scene, and (c) nowhere to turn: double rejection and identity threat. The data indicate that young British South Asian gay men may face multiple layers of rejection—racism and homophobia from the general population, homophobia from the ethnoreligious community, and racism from White British gay men. This can deprive young British South Asian gay men of the only remaining source of social support that they perceive—namely the sexual ingroup—inducing negative social and psychological outcomes for identity processes.